Present-day kinematics and seismic potential of the Ganzi-Yushu fault, eastern Tibetan plateau, constrained from InSAR - Zhao, Ningyuan; Ji, Lingyun; Zhang, Wenting; Xu, Xiaoxue; Wang, Jinshuo (Frontiers in Earth Science, 2023)
In recent years, earthquakes have occurred frequently on the southeastern edge of the Tibetan Plateau, and the seismic risk is high. However, because of the remote location of the Ganzi-Yushu fault zone, no high-resolution geodetic measurements of this region have been made. The radar line-of-sight deformation field of the Ganzi-Yushu fault was obtained using seven-track ascending and descending Sentinel-A/B interferometric synthetic aperture radar (InSAR) data from 2014 to 2020. Using the InSAR and published Global Navigation Satellite System (GNSS) data, we calculated the 3D deformation field in the study area, investigated the segment-specific fault slip rate, and inverted the fault slip distribution pattern using the steepest descent method. We then evaluated the seismic risk using the strain rate field and slip deficit rate. The main findings of this study include the following. (1) The slip rate of the Ganzi-Yushu fault gradually increases from 2.5 to 6.8 mm/yr from northwest to southeast. (2) A high-resolution strain rate map shows high-value anomalies in the Yushu and Dangjiang areas. (3) Our comprehensive analysis suggests that the seismic risk of the Dangjiang and Dengke segments with high slip deficits cannot be ignored.